Factors and Recommendations Related To Job Burnout: A Case of ABC University’s Lecturers - Yun, Pengfei; Preudhikulpradab, Sirichai (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
At present, teacher job burnout has become a major problem in the field of education. Over time, many people show anxiety and boredom about work. Job burnout refers to a state of physical and mental exhaustion produced under work pressure. The research site is at ABC University with two goals: 1. To examine the current job burnout situation at ABC University. 2. To propose some suggestions for improving job burnout at ABC University. This paper adopts a mixed-research approach, mainly collecting data through an online questionnaire. Data analysis includes descriptive statistics and content analysis. The actual sample was 170 respondents from ABC University, and 127 of the 170 respondents provided their suggestions in the open-ended question section. This study analyzes the factors that affect individual job burnout from the perspective of organizational behavior and hopes to put forward some suggestions to improve the job burnout situation at ABC University and bring a win-win for both individuals and organizations. Through the analysis of closed-ended questions, this study found that four factors: workload, workplace relationship, fairness, and job meaningfulness all impacted teacher job burnout. Through the analysis of open-ended questions, this study found that teachers’ job burnout can be reduced by increasing teachers’ wages, reducing teachers’ workload, providing teachers with a fair evaluation system, and providing teachers with more learning opportunities.